Synthesis, in vitro cytotoxicity, molecular docking and ADME study of some indolin-2-one linked 1, 2, 3-triazole derivatives. (April 2022) - Das, Arnika; Greco, Giulia; Kumar, Sujeet; Catanzaro, Elena; Morigi, Rita; Locatelli, Alessandra; Schols, Dominique; Alici, Hakan; Tahtaci, Hakan; Ravindran, Febina; Fimognari, Carmela; Karki, Subhas S.
Abstract: In pursuit of an anticancer lead, a library of 1, 2, 3-triazole derivatives (7a-x) was prepared, characterized and screened for in vitro cytotoxicity in different cell lines. Most of the compounds proved to be cytotoxic with IC50 values in the low micromolar range. Further studies showed that the most active compound 7c induces caspase-dependent apoptosis in Jurkat cells by activating both the intrinsic and the extrinsic apoptotic pathways and perturbs cell-cycle progression. Moreover, 7c did not show any genotoxic activity. Molecular docking simulations were performed against epidermal growth factor receptor (EGFR). Docking experiments showed that, compounds 7c, 7o and 7 v bind within active sites of epidermal growth factor receptor EGFR (Pdb ID: 6P8Q) by strong hydrogen bonds with residue MET793, Pi-Sulfur with residue MET790 and Pi-Alkyl type interactions with residues LEU788, ALA743 . The SwissADME webserver investigation suggested that most of the synthesized compounds follow the rules of drug-likeness. Graphical Abstract: ga1 Highlights: 24 indole linked 1, 2, 3-triazoles were prepared and screened for in vitro cytotoxicity in different cell lines. Compound 7c showed equipotent cytotoxic activity against CEM cells in comparison to melphalan standard. Further studies showed that most potent compound 7c induces caspase-dependent apoptosis in Jurkat cells. Docking experiments showed that, compounds namely 7c, 7o and 7v bind within active sites of EGFR (Pdb ID: 6P8Q). Moreover, compound 7c did not show any genotoxic activity. The SwissADME investigation suggested that most of the synthesized compounds follows the rules of drug-likeness.